HUBUNGAN PLACE ATTACHMENT DENGAN PERILAKU PROSOSIAL RELAWAN SOSIAL - Christy Christy; Riana Sahrani (Fakultas Psikologi Universitas Tarumanagara, 2016)
This study aimed to discover the correlation between place attachment and prosocial behavior among social volunteers, including who is still students (adolescent). Social volunteers are those who help others voluntarily. The activities they do can be classified as prosocial behavior, which means a set of voluntary action aimed at benefiting others. One’s action can be affected by environment and when one feels attach to the environment, one may form place attachment. Place attachment is an affective bond between a person to a place. Place attachment consists of two dimensions, in which both dimensions have different form of attachment. Place dependence can be formed if a place can fulfilled one’s goal. Whereas, place identity can be formed because a place has a symbolic meaning for a person. Result in this study showed that r = 0,043 and p < 0,198; which means there is no correlation between place dependence and prosocial behavior among social volunteers. Result in this study also showed that r = 0,266 and p = 0,000; which means place identity has a positive correlation with prosocial behavior among social volunteers.Keywords: Place attachment, prosocial behavior, social volunteers